PENANAMAN SIKAP TOLERANSI SOSIAL SISWA MELALUI PEMBELAJARAN IPS PADA KELAS VIII DI SMP ISLAM PLUS AL IKHLAS TAQWA - Sari, Cindi Nurmala (Islamijah: Journal of Islamic Social Sciences, 2024)
The purpose of this research is to describe 1) Cultivation of social tolerance attitudes of students through social studies learning class VIII at SMP Islam Plus Al Ikhlas Taqwa, and 2) Supporting and inhibiting factors for the cultivation of tolerance attitudes of VIII grade students at Al Ikhlas Taqwa Islamic Plus Junior High School. This research methodology uses qualitative methods. The data collection technique is through observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. The results showed that 1) Cultivation of social tolerance attitudes of students through social studies learning is by linking social studies learning materials with the material Plurality of Indonesian Society, by studying the material then students can understand to be tolerant, and on the material students can discuss it in groups, and by providing a good example in tolerance. 2) The driving factors in instilling tolerance are school policies, a sense of caring, and respect for differences. The inhibiting factors are selfishness and choice in making friends.Keywords: Social Tolerance Attitude, Social Studies Learning